Adapting US service learning projects to other cultures: dementia and memory care in the Dominican Republic - Christine A Tisone; Idethia S Harvey (Elsevier, 2018)
Background: Caring for older populations with dementia is a global challenge. The cultural context in which ageing occurs is an important factor that influences treatment and daily care strategies for those with dementia, including location (home or health-care facility) and choice of caretakers (family members or health-care personnel). We adapted a successful US memory care service learning project for university students in the USA to pilot test in the Dominican Republic. Methods: 18 health majors from Texas A&M University participated in a special topics course dedicated to culture, ageing, and dementia. The group spent 2 weeks in Jarabacoa, Dominican Republic, immersed in the culture, studying, and volunteering at a local assisted-living facility. Five memory care sessions (3-h each) were held with the same 25 residents over the 2-week period. The principal activities were spice-painting (a technique which triggers the olfactory sense and stimulates parts of the brain associated with long-term memory) and life story interviews. Findings: The staff and residents of the assisted-living facility demonstrated great appreciation for our presence and for the engaging activities. Staff reported that they do not have the human resources necessary to conduct similar activities. Furthermore, they confirmed that, within the Dominican culture, most older people are cared for in their homes, and that there is a stigma associated with sending loved ones to this type of facility. This affects the resources available to the facility. Student evaluations and reflective essays completed after their experience indicated enthusiasm for the project (100% highly satisfied), personal growth, and appreciation for the cultural immersion opportunity. Interpretation: In May, 2018, we will adapt the project to better fit the needs of the Dominican health system by partnering with a Dominican university, thus creating a sustainable volunteer system. We will also expand to include families in the area that are caring for their older relatives with dementia in their homes, by conducting home visits and community education sessions; in this way, families can learn the memory care activities and conduct them on their own. Funding: None.